ANALYSIS OF LANGUAGE COMPLIANCE IN THE FILM PEREMPUAN TANAH JAHANAM AS A REPRESENTATION OF JAVA CULTURE - Afina Naufalia; Wulan Fajrideani (Lembaga Penelitian Universitas Pasundan, 2022)
The Film is a tool to convey various messages to the general public through communication or dialogue. In communication, in addition to paying attention to context, speakers must also have politeness in their language. Everyone's language politeness is different, depending on the context or speech situation and social distance between individuals, especially if it is associated with culture. Every culture has different standards of politeness. This study aims to examine language politeness as a representation of Javanese culture in the film Perempuan Tanah Jahanam by Joko Anwar. The principle of politeness in the language is based on Leech's theory which consists of (1) the maxim of wisdom, (2) the maxim of generosity, (3) the maxim of praise, (4) the maxim of humility, (5) the maxim of compatibility, and (6) the maxim of sympathy. The method used in this research is the descriptive qualitative method. The data collection technique in this research used the Listen Free Libat Cakap (SBLC) technique and the notetaking technique as further research techniques. Based on the results of data analysis, it can be concluded that there are violations and fulfillment of politeness principles in this film's dialogue. Most show the fulfillment of the maxims of wisdom and praise, while the maxims of humility and sympathy are often violated. The results of this study can represent politeness in Javanese culture. it can be concluded that there are violations and fulfillment of politeness principles in this film's dialogue. Most show the fulfillment of the maxims of wisdom and praise, while the maxims of humility and sympathy are often violated. The results of this study can represent politeness in Javanese culture. it can be concluded that there are violations and fulfillment of politeness principles in this film's dialogue. Most show the fulfillment of the maxims of wisdom and praise, while the maxims of humility and sympathy are often violated. The results of this study can represent politeness in Javanese culture.